Formulation, Evaluation and Optimization of Self-Nano Emulsifying Drug Delivery System Containing Felodipine - Dabhi, Mahesh; Patel, Snehal; Mori, Dhaval; Patel, Dhaval; Patel, Nilesh; Parmar, Ramesh (Micro and Nanosystems, 2014)
The aim of the present investigation is to develop a stable formulation for Self-Nanoemulsifying Drug Delivery System (SNEDDS) in order to enhance the solubility and release rate of poorly soluble drug (felodipine). Solubility study was performed to select the oil, surfactant and co surfactant in which the drug is had highest solubility. The pseudo-ternary phase diagram was constructed to study the effect of change in a ratio of surfactant/co-surfactant on nanoemulsion formulation and to find emulsification area in phase diagram. The simplex lattice design was used to optimize the formulation and each formulation was evaluated for various physico-chemical formulation parameters like turbidimetric evaluation, droplet size analysis, drug content, effect of dilution and aqueous phase composition, viscosity, pH and self-emulsification. The results indicate that optimized fomulation as per simplex lattice design contained 23.81% oil (Labrafac PG), 57.14% surfactant (Cremophor EL) and 19.05% co-surfactant (PEG-400) having mean droplet size 26.13 nm, emulsification time 13 seconds, and % transmittance 99%. In vitro drug release indicates that more than 80% drug was released in less than 3 min.
Keywords: pseudo-ternary phase diagram